2019
DOI: 10.21638/spbu03.2019.306
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbiome in chronosequence of spoil heaps of Kursk Magnetic Anomaly

Abstract: The physicochemical parameters, vegetation and biodiversity of microbiomes inhabiting 10-, 35- and 50-year-old embryonic soils (technozems) formed in the mining areas of the Kursk Magnetic Anomaly (Russia) were analyzed in the current study. Analysis of taxonomic diversity was carried out by 454-pyrosequencing of the V4 variable region of the 16S rRNA gene. All points of the chronosequence were characterized by microbiomes reliably differing in taxonomic composition. The older the dump, the higher the proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…It also suggests that the use of biowaste, as a technique to support the remediation of degraded post-mining soils, besides the delivery of exogenic organic carbon, is also a source of valuable microorganisms whose presence in the soil affects, among others, the soil structure [85]. While in our study we noted an exact influence of the initial application of organic matter into soil remediation on the microbial community, other studies suggested that the remediation age [86], and age of the stand [87] influence soil microorganisms. Therefore, the higher number of microorganisms at longer remediated areas may result from the higher amount of litter provided by the higher biomass of stand.…”
Section: Effect Of Initial Application Of Sewage Sludge and Its Non-a...supporting
confidence: 37%
“…It also suggests that the use of biowaste, as a technique to support the remediation of degraded post-mining soils, besides the delivery of exogenic organic carbon, is also a source of valuable microorganisms whose presence in the soil affects, among others, the soil structure [85]. While in our study we noted an exact influence of the initial application of organic matter into soil remediation on the microbial community, other studies suggested that the remediation age [86], and age of the stand [87] influence soil microorganisms. Therefore, the higher number of microorganisms at longer remediated areas may result from the higher amount of litter provided by the higher biomass of stand.…”
Section: Effect Of Initial Application Of Sewage Sludge and Its Non-a...supporting
confidence: 37%
“…The findings of Barliza et al [34] in spoil heap reclaimed from an opencast coal mine in Colombia indicates that the highest fine litterfall recorded in the 21-year-old site (2.3 Mg ha −1 year −1 ) was more than double that recorded in the 7-year-old site (1.1 Mg ha −1 year −1 ) and concluded the enriching role of litterfall on soil organic matter content and nutrient status with the increasing age of the stand. An increase in the age of the stand also increases the microbial community [35], which results in the decomposition of organic matter and increases the amount of carbon in the soil with increasing age. Mukhopadhyay et al [36] also concluded that age of reclamation has a significant effect on the nutritional and microbial properties of the mine soils.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial community is an important component in soil development processes. There are several studies of the microbiome of disturbed soils using highthroughput sequencing methods [5,10,11]. Despite it, this theme is far from generalization.…”
Section: Introductionmentioning
confidence: 99%